2005
DOI: 10.1007/s10712-005-1836-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Electromagnetic Modelling and Inversion from Theory to Application

Abstract: The whole subject of three-dimensional (3-D) electromagnetic (EM) modelling and inversion has experienced a tremendous progress in the last decade. Accordingly there is an increased need for reviewing the recent, and not so recent, achievements in the field. In the first part of this review paper I consider the finite-difference, finite-element and integral equation approaches that are presently applied for the rigorous numerical solution of fully 3-D EM forward problems. I mention the merits and drawbacks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(98 citation statements)
references
References 146 publications
(148 reference statements)
1
96
0
1
Order By: Relevance
“…Therefore, at some large enough distance of the boundaries from the anomalous domain, we may neglect the values of the anomalous field at the boundaries (including those located above the sea level in the air). However, in a general case, a more accurate boundary condition can be used (e.g., Zhdanov, 2002;Avdeev, 2005;Newman, 2014). …”
Section: Formulation Of a Hybrid Fd-ie Methods Fd Modeling Of The Anommentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, at some large enough distance of the boundaries from the anomalous domain, we may neglect the values of the anomalous field at the boundaries (including those located above the sea level in the air). However, in a general case, a more accurate boundary condition can be used (e.g., Zhdanov, 2002;Avdeev, 2005;Newman, 2014). …”
Section: Formulation Of a Hybrid Fd-ie Methods Fd Modeling Of The Anommentioning
confidence: 99%
“…There are several popular numerical approaches for 3D EM modeling: integral-equation (IE), finite-difference (FD), and finiteelement (FE) methods (Zhdanov, 2002(Zhdanov, , 2009(Zhdanov, , 2015Avdeev, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also require storing merely several pairs of so-called correction vectors that dramatically diminish the storage requirements. A more complete review on this subject may be found in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Techniques that succeed in relatively inaccurate solutions to inverse problems combine the forward and inverse design step and iterate it numerous times. A survey of such schemes is presented in [44,45] -in summary, best known systems achieve to solve some ill-defined inverse problems with prior knowledge of solution structure for K ≈ 10 3 in substantial amount of time. As formal analysis of such methodologies is not provided, we conjecture that solving Pr.1 is a task which is well beyond reach of modern inverse design tools.…”
Section: Inverse Designmentioning
confidence: 99%